Exploring Animal Encounters Philosophical, Cultural, and Historical Perspectives (Palgrave Studies in Animals and Literature, 2018)
This collection of essays offers multifaceted explorations of animal encounters in a range of philosophical, cultural, literary, and historical contexts. Exploring Animal Encounters encourages us to think about the richness and complexity of animal lives and human-animal relations, foregrounding the intricate roles nonhuman creatures play in the always already more-than-human sphere of ethics and politics. In this way, the essays in this volume can be understood as a contribution to alternative imaginings of interspecies coexistence in a time in which the issue of human relations with earth and earth others has come to the fore with unprecedented force and severity.